Heating ventilation and air-conditioned configurations for hotelsan approach review for the design and exploitation. (November 2020) - Torres, Yamile Díaz; Herrera, Hernán Hernández; Plasencia, Mario A. Alvares Guerra; Novo, Eduardo Pérez; Cabrera, Lester Pimentel; Haeseldonckx, Dries; Silva-Ortega, Jorge Iván
Abstract: The tourism sector is one of the main worldwide economic sectors with sustained growth, demonstrating its strength and resilience. In this sector, energy uses have increased to ensure quality, guest comfort, and rate level requirements being a building with great energy consumption. Several factors influence and can produce a significant variation in hotel consumption even in facilities located in the same region; the difference in a four-star hotel can reach 114 kWh/m 2 /year. This paper deals with related aspects such as hotel design, operation, type of service, occupancy patterns, operating point and efficiency of a heating, ventilation, and air conditioning (HVAC) system where 30 to 50% of the energy is consumed. Also, previous works based on the implementation of non-conventional energy resources such as photovoltaics projects to replace fuel dependence and high costs in electricity bills were reviewed. where there are savings of up to 30% in electricity and 60% in gas consumption. However, the initial capital investment and payback period are high and require new features to be considered in these facilities.